PENGARUH PELAYANAN PURNA JUAL TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA PT JAYA INDAH MOTOR CABANG JAMBI - Ahmad Tarmizi (Universitas Batanghari Jambi, 2016)
PT. Jaya Indah Motor must always try and commit to supporting all marketing activities that are run. In addition to presenting the procurement of a quality product with a selection of the best machines, spare parts of high quality original (partsupport), remanufacturing, also provides the assurance of reliable after-sales service(service support & full maintenance contract). To support the Service post-sale PT. Jaya Indah Motor. Post-sale service provided is training service maintenance, repair and maintenance (product service support), maintenance of full (full maintenance contract) and the provision of spare parts (part support).Primary data is the main data needed in research and obtained from respondents who became the object of this research. The collection is done by means of a detailed questionnaire. The source is a consumer PT. Jaya Indah Motor as much as 100 respondents.The statement declared that